Study the Antibacterial and Antibiofilm Activity of Purified Exopolysaccharides (EPSs) from Lactobacillus acidophilus Against Bacteria Isolated from Burn Wounds - Noor Naeem Khwen (Journal of Global Pharma Technology, 2019)
The current study was investigated the antibacterial and antibiofilm activity potential of purified Exopolysaccharides (EPSs) from lactobacillus acidophilus against bacteria isolated from patients with Burn wounds that showed some resistance to antibiotics, the results of isolation and identification were showed the predominant bacteria was S. aureus 90% followed by P.aeruginosa 80%, B.subtilis 60%, S.hominis 50%, E coli 40%, P.mirabilis 40%, E.feacalis 40%. Furthermore some isolates were sensitive to ciprofloxacin, P.aeruginosa 37.5%, S. hominis 100%, B. subtilis 16.6%, E.feacalis 50%, P.mirabilis 100%, However the other isolates showed sensitivity to Tetracycline such as S.aureus 44.4 %, E.coli 100%, B. subtilis 100 %. While Azithromycin and Novobiocin, Ampicillin, Cefotaxime, Erythromycin, Imipenem, Doxycycline were showed no effect toward isolates .Meanwhile Chloromphenicol, Amoxicillin /clavulanic acid, Gentamicin showed intermediate effects toward isolates. In addition EPSs showed a positive antibacterial activity against the isolates with different concentrations and the highest value recorded in 500 mg/ml concentration in each isolates but in 200mg/ml concentration in some isolates showed no inhibition zones. Finally anti biofilm activity of EPSs, the study noticed   EPSs showed more effective against biofilm formation withing 24 hr  more than  performed biofilm of isolates (after 24 hr). Furthermore MIC of antibiotic showed more effective  than MIC of EPSs in biofilm assay, but both MIC of antibiotic and EPSs were decreased the strength of biofim of isolates from strong biofilm and  moderate biofilm  formation to weak biofilm formation. The study was revealed depended on obtained results, purified EPSs from Lactobacillus acidophilus had antibacterial and antibiofilm activities against some bacteria isolated from burn wounds showed some resistance to antibiotics.Keywords: Extraction of Exopolysaccharides from lactobacillus acidophilus, Antibacteria, Antibiofilm activity of EPS, Burn wounds.